Minimum wage in Peru. When did they become unimportant? - Yamada, Gustavo; Bazán, Ernesto (Universidad del Pacífico, 1994)
This paper studies the minimum wages' impact in the Peruvian economy through causality tests with time series available. It finds that minimum wages have lost all importance in the labor market both in a "populist" government (1985-1990), and in a "market-friendly" administration (1990-1993). The second case is not surprising at all, because it is consistent with the "laissez-faire" ideology in the current administration. The first result, on the contrary, is an ironical and contradictory one with the income redistribution goals aimed by former President García.